PEMANFAATAN BIJI KELOR (Moringa oleifera Lamk.) SEBAGAI BIOFLOKULAN LOGAM BERAT Hg, Pb DAN Cr PADA LIMBAH CAIR INDUSTRI KERAMIK DINOYO MALANG - Evika Sandi Savitri, Eny Yulianti (El-QUDWAH, 2006)
The research is conducted on the effectiveness of Moringa oleifera as “bioflokulan” of Hg, Pb, and Cr to liquid waste of ceramics industry in Dinoyo Malang. It includes the analysis of chemical and physical nature of the liquid waste and also the effect of adding Moringa oleifera to the liquid sample of Hg, Pb, and Cr. The research on physical nature shows that liquid waste of ceramics industry in Dinoyo Malang is turbid, odorless and it has white colour, 25.3 C temperature, 258 S conductivity and TDS 185 ppm. While the research on the chemical nature shows that it has pH 7.8, Hg and Pb are unidentified, and Cr 0.0402ppm. Both analyses indicate that they are below the limit line. The analysis also shows that there is significant concentration decrease after adding Moringa oleifera to the sample of Hg, Pb, and Cr, and this happen because Moringa oleifera contains 4-alfa-4-rhamnosiloxy-benzil-isothiosianat that can coagulate ions in metal.Kata kunci :  Moringa oleifera, bioflokulan, limbah cair industri keramik